3D radially-grown TiO2 nanotubes/Ti mesh photoanode for photocatalytic fuel cells towards simultaneous wastewater treatment and electricity generation. (25th December 2022) - Liu, Yuxin; Chen, Rong; Zhu, Xun; Ye, Dingding; Yang, Yang; Li, Jinwang; Wang, Dechao; An, Liang; Liao, Qiang
Abstract: Photocatalytic fuel cell (PFC) represents a clean environment and energy technology to directly recover chemical energy contained in wastewater for electricity generation by using solar energy. It is advantageous for the PFC to adopt the TiO2 nanotube array photoanodes that usually grow on planar Ti substrates. But low specific surface area and light utilization limit the improvement in the PFC performance. This work is directed to the development of a 3D radially-grown TiO2 nanotubes/Ti mesh photoanode. The Ti mesh substrate provides a large specific surface area for growing TiO2 nanotubes and benefits light scattering, while TiO2 nanotubes with high length-diameter ratio enhances electron transfer. Because of these merits, the staggered PFC with the 3D radially-grown TiO2 nanotubes/Ti mesh photoanode yields a maximum power density ( P MAX ) of ∼0.074 mW/cm 2, which is about 6.2 and 1.6 times as those with the TiO2 nanoparticles/Ti mesh and TiO2 nanotubes/Ti foil photoanodes, respectively. Increasing the mesh density of Ti mesh is synergic to improve the cell performance due to increased surface area and light utilization. The optimal P MAX of the ordinary PFC reaches as high as 0.15 mW/cm 2 when using the Ti mesh of 300 per inch. Notably, using Ti mesh as a substrate makes it easy to integrate multiple Ti meshes to form a stacked 3D photoanode, which shows excellent performance when feeding various pollutants even with biogas slurry. Besides, good stability of the developed photoanode is also demonstrated. This work offers an innovative strategy for developing high-performance 3D structured photoanode for photoelectrochemical systems. Highlights: TiO2 nanotubes are radially grown on Ti mesh via electrochemical anodization. Grid structure of Ti mesh provides large specific area and benefits light scattering. Ordinary PFC yields better performance than staggered PFC. Large mesh density improves the performance of the developed photoanode. Integration of multiple Ti meshes forms a stacked 3D photoanode.